(untitled) (Revista de História Regional, 2007)
The 17th century was a period of intense conflict between Portuguese and Spain, due to the end of the Iberian Union, in the year 1640. In this context, we can stress the personality of Father Antonio Vieira, who due to his relationship with D. João IV presents a series of economic projects to be implanted in America. Among those that were successful, we can point out the Implantation of the Company of Western Commerce that begins its activities in 1647. A predominant factor in Vieiras speech is the need to use the Jewish money for the execution of his projects; for the Jesuit this would be the only way for Portugal to win its war against Spain and balance its accounts. Another important factor and conflict generator is Vieiras defense of the idea that everyone, including the nobles, should pay tribute to the Crown. Starting form these conflicts, I intend to demonstrate how Father Antonio Vieira understood the Portuguese Economy at the time to the Restoration, highlighting the actions that had, or could have, influence in the Portuguese America, understanding the Jesuit as a representative of a mercantile thought that would be in conflict with other developing economic models.